To drive or not to drive? A qualitative comparison of car ownership and transport experiences in London and Singapore. (September 2019) - Chng, Samuel; Abraham, Charles; White, Mathew P.; Skippon, Stephen
Abstract: Cities are responding to their growing transportation demands in different ways. We interviewed city dwellers in two cities, Singapore and London, with highly developed transport infrastructure to understand individual transport decisions and experiences in the context of two different city cultures that support distinct transport policies. Compared to London, cars and other private transport are valued and priced beyond the reach of most in Singapore. Seventeen adults from London and sixteen from Singapore were interviewed and presented with an overview of the other city's transportation system to elicit their opinions on the differences and whether an alternate system could be applied in their city. Differences were observed in perceptions of, and beliefs concerning, private transport. In Singapore, cars served more than utilitarian purposes and were viewed as socially desirable status and success symbols. In London, car ownership and usage were viewed as a necessity due to a perceived lack of accessible, alternative transport. Both samples valued accessibility, affordability and comfort in relation to transport mode choice. There was also general acknowledgement and support for managing the car population and use in both cities, though how it should be done remains highly context-specific. Our findings suggest that public engagement and effective communication are important components when interventions and policies are introduced to better manage the car population and use in cities. Highlights: We explored car ownership and transport experiences in London and Singapore. Accessibility, affordability and comfort were common transport considerations. Differences were observed in perceptions of, and beliefs concerning, cars and car use. Distinct geographical constraints led to different evaluations of transport policies. Public engagement and education are important when implementing transport policy.